Causes and Timing of Nonelective Reoperations after Bariatric Surgery: A Review of 1304 Cases at a Single Institution. Issue 10 (October 2015) - Thompson, Erin; Ferrigno, Lisa; Grotts, Jonathon; Knox, Jenna; Sobelman, Samantha; Thoman, David; Bounoua, Farida; Zerey, Marc
As the number of patients undergoing bariatric procedures for weight loss increases, an understanding of the causes and timing of complications requiring reoperation is critical. The aim of our study was to characterize the type and timing of nonelective (NE) reoperations in these patients. Over five years, 1304 patients undergoing index procedures were identified: 769 laparoscopic Roux-en-Y gastric bypasses (LRYGB), 301 laparoscopic sleeve gastrectomies, and 234 laparoscopic adjustable gastric bands. We identified 117 NE reoperations, which were grouped by index procedure as well as whether they occurred early (≤90 days) or late (>90 days). In the laparoscopic adjustable gastric bands group, slipped gastric band was the most common indication for early (n = 2) and late (n = 2) reoperations. Biliary disease was the most common cause for early reoperations (n = 4), and the only cause for late reoperations (n = 2) after laparoscopic sleeve gastrectomies. For LRYGB, diagnoses differed between the early and late groups, with the most common early indications being bowel obstruction (n = 8) and anastomotic leak (n = 4) of the 18 early reoperations, and internal hernia (n = 36) and biliary disease (n = 17) of the 82 late reoperations. The vast majority of NE reoperations were performed laparoscopically (92%), with conversions and primarily open procedures only occurring in the LRYGB group.